The Effect Of Mirror Therapy On Increasing Muscle Strength In Stroke Non Haemoragic Patients In The Bougenville Room - Nunung Liawati; Widiasty Agustin; Ida; Ady Waluya (HealthCare Nursing Journal, 2025)
Stroke is a health problem that is the main cause of disability at a young age. In developing countries, stroke ranks third as the main cause of death after heart disease and cancer. The aim of the research was to determine the effect of mirror therapy on increasing muscle strength in stroke patients. Stroke is a functional brain disorder that can impact various body functions, including motor deficits in the form of hemiparesis. Mirror therapy is a therapy for stroke patients that involves the mirror neuron system. This type of research is pre-experiment with one group pretest and posttest design. The population was all non-hemorrhagic stroke patients with a sample of 17 patients, using a purposive sampling technique. Data analysis used was the Wilcoxon test with a normality test using Shapiro Wilk. The research results showed that the average muscle strength before the intervention was 3.06 after the intervention was 4.00. The results of analysis using the Willcoxon test obtained a p value for muscle strength of 0.002 < 0.05. This means that H0 is rejected, there is an effect of mirror therapy on increasing muscle strength in non- hemorrhagic stroke patients. Mirror Therapy has an effect on increasing muscle strength in stroke patients with hemiparesis, so the mirror therapy technique can be used as management and treatment to increase muscle strength in stroke patients